850 OBJECTIVE IDENTIFICATION OF OESOPHAGEAL ADENOCARCINOMA USING MASS SPECTROMETRY IMAGING. (17th September 2021) - Antonowicz, Stefan; Nima, Abbassi-Ghadi; McKenzie, James; Kumar, Sacheen; Huang, Juzheng; Jones, Emrys; Strittmatter, Nicole; Pitts, Gemma; Kudo, Hiromi; Goldin, Rob; Hoare, Jonathan; Veselkov, Kirill; et al.
Abstract:  : Outcomes for oesophageal adenocarcinoma continue to be poor, as patients are often diagnosed too late for curative treatment. New tools to assist early and rapid diagnosis are needed. Tissue phospholipids quantified by mass spectrometry imaging (MSI) can objectively diagnose non-oesophageal cancers from control tissue in minutes. However, whether MSI can objectively identify oesophageal adenocarcinoma is unknown and represents a significant challenge, as this microenvironment is complex with phenotypically similar tissue-types. Methods: Desorption electrospray ionisation mass spectrometry imaging (DESI-MSI) and bespoke chemometrics were used to assess the phospholipidomes of oesophageal adenocarcinoma and relevant control tissues, in surgical (discovery) and endoscopic (validation) cohorts. Structural annotations verified by tandem MS fragmentation patterns were performed to understand the characteristics of the key differential phospholipids. Bioinformatics, quantitative polymerase chain reaction, and immunohistochemistry were performed to describe the reprogramming of phospholipogenesis in oesophageal adenocarcinoma. Finally, genetic silencing experiments were performed to understand whether this genetic reprogramming impacts the oesophageal adenocarcinoma phospholipid signature. Results: Multivariable models based on tissue phospholipids from 117 patients were highly discriminant for oesophageal adenocarcinoma both in discovery (area-under-curve = 0.97) and validation cohorts (AUC = 1). Cancer samples were enriched for polyunsaturated phosphatidylglycerols with longer acyl chains, with stepwise enrichment in pre-malignant tissues. Expression of fatty acid and glycerophospholipid synthesis genes was significantly upregulated, and characteristics of fatty acid acyls matched phospholipid acyls. Mechanistically, reducing ACLY expression in oesophageal adenocarcinoma cells shortened GPL chains, therefore linking de novo lipogenesis to the oesophageal adenocarcinoma phospholipidome. Conclusion: DESI-MSI (i) objectively identified invasive oesophageal adenocarcinoma from a number of pre-malignant tissues (ii) described the characteristics of cancer phospholipids, which have unknown function (iii) unveiled a new mechanism of phospholipidomic reprogramming. These results call for accelerated diagnosis studies using DESI-MSI in the upper gastrointestinal endoscopy suite, as well as functional studies to determine how polyunsaturated phosphatidylglycerols are generated, and how they contribute to oesophageal carcinogenesis.